Management of Plastic Packaging Waste Crisis During the Covid-19 Epidemic Situation - Yamakanith, Purinat; Sanont, Rujikarn (Journal of Human and Society, Sisaket Rajabhat University, 2022)
The purpose of this article writing is to make readers think about the problem of plastic packaging waste that is increasing during the Covid-19 epidemic situation and to know how to manage plastic packaging waste in a systematic way in order to find the way to develop sustainable packaging alternatives in the COVID-19 era. Due to the epidemic of the COVID-19 virus in 2020, the amount of plastic waste resulting from food and beverage packaging has increased dramatically. The epidemic of the virus reappears in 2021, the situation of plastic packaging waste continues to escalate and affect society and quality of life. For this reason, governments, businesses and people should be aware of the situation of plastic packaging waste by working together to find a way to systematically solve the plastic packaging waste problem towards a sustainable circular economy after the COVID-19 epidemic situation has ended.